(untitled) (Journal of the Management Sciences, 2024)
This paper examined the effects of Foreign Direct Investment (FDI) on the Economic growth in Nigeria 1985-2019). The study employed the use of Ordinary Least Square (OLS) regression technique to test the time series data from 1985 – 2019. The was set to know the degree of the relationship that exist foreign direct investment and economic growth (gross domestic product) in Nigeria. The regression analysis results showed that there is a significant link between FDI and economic growth in Nigeria as suggested by extant previous literature. It was recommended that Nigeria should ensure a stable political system, with friendly economic policies to stimulate the growth and expansion of foreign direct investments in Nigeria. Secondly, Nigeria should pursue trade liberalization and open up her economy.